Eccentric and Isometric Hip Adduction Strength in Male Soccer Players With and Without Adductor-Related Groin Pain: An Assessor-Blinded Comparison. Issue 2 (14th February 2014) - Thorborg, Kristian; Branci, Sonia; Nielsen, Martin Peter; Tang, Lars; Nielsen, Michael Bachmann; Hölmich, Per
Background: Adductor-related pain is the most common clinical finding in soccer players with groin pain and can be a long-standing problem affecting physical function and performance. Hip adductor weakness has been suggested to be associated with this clinical entity, although it has never been investigated. Purpose: To investigate whether isometric and eccentric hip strength are decreased in soccer players with adductor-related groin pain compared with asymptomatic soccer controls. The hypothesis was that players with adductor-related groin pain would have lower isometric and eccentric hip adduction strength than players without adductor-related groin pain. Study Design: Cross-sectional study; Level of evidence, 3. Methods: Male elite and subelite players from 40 teams were contacted. In total, 28 soccer players with adductor-related groin pain and 16 soccer players without adductor-related groin pain (asymptomatic controls) were included in the study. In primary analysis, the dominant legs of 21 soccer players with adductor-related groin pain (≥4 weeks duration) were compared with the dominant legs of 16 asymptomatic controls using a cross-sectional design. The mean age of the symptomatic players was 24.5 ± 2.5 years, and the mean age of the asymptomatic controls was 22.9 ± 2.4 years. Isometric hip strength (adduction, abduction, and flexion) and eccentric hip strength (adduction) were assessed with a handheld dynamometer using reliable test procedures and a blinded assessor. Results: Eccentric hip adduction strength was lower in soccer players with adductor-related groin pain in the dominant leg (n = 21) compared with asymptomatic controls (n = 16), namely 2.47 ± 0.49 versus 3.12 ± 0.43 N·m/kg, respectively ( P < .001). No other hip strength differences were observed between symptomatic players and asymptomatic controls for the dominant leg ( P = .35-.84). Conclusion: Large eccentric hip adduction strength deficits were found in soccer players with adductor-related groin pain compared with asymptomatic soccer players, while no isometric strength differences were observed between the groups.